2011
DOI: 10.1016/j.nucengdes.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of numerically determined linear stability boundaries of a supercritical heated channel

Abstract: The large change in density which occurs when supercritical water is heated above or near to the pseudocritical temperature in a vertical channel can result in the onset of flow instabilities (density wave oscillations). Near to the critical point, substance properties such as enthalpy, density, viscosity… all have larger relative uncertainties compared to subcritical conditions. The goal of this study is to quantify the effect of these property uncertainties and system uncertainties on numerically determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The experimental research work recently carried out by Xiong et al (2012) and several numerical studies (Chatoorgoon, 2001;Gómez et al, 2008;Jain and Rizwan-uddin, 2008;Ambrosini and Sharabi, 2008;Sharabi et al, 2008;Ambrosini, 2009;Zhao et al, 2011;T'Joen et al, 2011;Ambrosini, 2011;Ampomah-Amoako and Ambrosini, 2013;Xiong et al, 2013) confirmed the possibility of flow induced DWOs for various fluids operating at supercritical conditions. The out-of-phase mode of oscillations in two parallel channels at supercritical conditions were experimentally observed by Xiong et al (2012) and then, the study was followed by a numerical investigation (Xiong et al, 2013) using a 1-D thermalhydraulic (TH) model.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…The experimental research work recently carried out by Xiong et al (2012) and several numerical studies (Chatoorgoon, 2001;Gómez et al, 2008;Jain and Rizwan-uddin, 2008;Ambrosini and Sharabi, 2008;Sharabi et al, 2008;Ambrosini, 2009;Zhao et al, 2011;T'Joen et al, 2011;Ambrosini, 2011;Ampomah-Amoako and Ambrosini, 2013;Xiong et al, 2013) confirmed the possibility of flow induced DWOs for various fluids operating at supercritical conditions. The out-of-phase mode of oscillations in two parallel channels at supercritical conditions were experimentally observed by Xiong et al (2012) and then, the study was followed by a numerical investigation (Xiong et al, 2013) using a 1-D thermalhydraulic (TH) model.…”
Section: Introductionmentioning
confidence: 78%
“…The solution algorithms developed by Jain and Rizwan-uddin (2008) and Xiong et al (2013) are similar to those used in SPORTS. DWOs for supercritical fluids have also been analyzed by several other researchers (Gómez et al, 2008;Ambrosini and Sharabi, 2008;Sharabi et al, 2008;Ambrosini, 2009;Zhao et al, 2011;T'Joen et al, 2011;Ambrosini, 2011;Ampomah-Amoako and Ambrosini, 2013) using 1-D TH models. In most of these 1-D TH models, the dependence of the thermodynamic properties on the pressure is neglected and the density changes with the enthalpy only, which leads to decoupled momentum and energy conservation equations and the flow is treated as incompressible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high power-to-mass flow rate ratio in SCWRs, which results in the improvement in the thermal efficiency, will cause significant reduction in the density of the water across the core similar to boiling water reactors (BWRs) and thus, strains the reactor control mechanism and increases the potential for the reactor to be susceptible to self-sustained density wave oscillations (DWOs). Several studies [2][3][4][5][6][7][8][9][10][11][12][13] confirmed the possibilities of existence of DWO for various fluids, H 2 O and CO 2 , undergoing forced or natural flow circulation under supercritical conditions. On the other hand, the DWOs, which are caused by nonlinear interactions among the various thermal and flow variables, may considerably be influenced by the nuclear coupled density and temperature reactivity feedback effects leading to power oscillations in addition to the flow oscillations.…”
Section: Introductionmentioning
confidence: 87%
“…The results confirmed the existence of flow oscillations at some operating conditions and the predicted instability thresholds obtained by different approaches agreed well. T'Joen et al [11], using the channels described by Ambrosini and Sharabi [7], predicted stability boundaries by the eigenvalue analysis of the linearized set of perturbed equations. Ampomah-Amoako and Ambrosini [13] predicted DWOs for fuel-bundle slices using another CFD program, STAR-CCM+, for supercritical water.…”
Section: Introductionmentioning
confidence: 99%